Tax Management Strategy for Company Operational Effectiveness - Wibowo, Imam (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
Within a dynamic and intricate corporate environment, the strategic significance of tax management is progressively crucial in guaranteeing operational continuity and fostering company growth. This study aims to examine the influence of tax management on the operational efficiency of companies. This study employs a qualitative methodology utilizing descriptive techniques. The research findings indicate that implementing a proficient Tax Management plan has a beneficial influence on the operational efficiency of manufacturing enterprises. Companies that effectively utilize tax deductions and incentives, strategically plan their financial structures, and implement a comprehensive tax management system are more likely to achieve greater operational cost efficiency. Engaging in partnerships with external tax specialists has been demonstrated to offer valuable perspectives and professional guidance. Additionally, regularly monitoring alterations in tax legislation enables organizations to foresee their consequences and adapt tax plans in advance. Hence, the research findings validate that implementing intelligent Tax Management can serve as a crucial determinant in enhancing manufacturing organizations' operational and financial efficacy.